Groundwater lowering in construction : a practical guide to dewatering - Cashman, P. M. (Applied geotechnics ;, 2013)
"Construction requires dry, stable and safe soil conditions, which frequently requires the reduction of pore pressures or groundwater levels. This established professional guide covers the design, construction and environmental management of groundwater control and dewatering works for construction projects. It is practically oriented and written for practising construction professionals, whether engineers, geologists or hydrogeologists, and Masters level students. It is well illustrated with case studies. Changes have been made to this new edition to reflect the considerable developments in environmental management practice and procedures and in the regulations related to groundwater control. The book contains a brand new chapter on permanent dewatering systems, and heavily revised coverage of other dewatering systems, environmental impacts, and the design of groundwater lowering systems, and coverage of specialist topics such as the management of water from sump pumping and wellpointing for deeper excavations"--